2019
DOI: 10.1055/s-0039-1700597
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Ferritin as a Prognostic Marker in Acute Hemorrhagic Stroke

Abstract: Background Acute hemorrhagic stroke (AHS) resulting from intracerebral hemorrhage (ICH) is a rampant neurological disorder with devastating consequences, particularly in Indians. Recently, serum ferritin levels have been related to adverse cardiovascular and stroke outcomes. We aimed to evaluate the prognostic utility of serum ferritin in AHS. Materials and Methods Admission serum ferritin levels were estimated in 50 AHS patients with primary supratentorial hemorrhage. Study subjects were categorized based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…22,46 Similarly, an independent association of high admission serum ferritin levels with unfavorable outcomes has been found in patients with intracerebral hemorrhage. 47,48 In our study, the iron overload status was more pronounced in nonsurvivors, but it was not associated with hemorrhagic transformation or disability. Transferrin levels were lower in untreated patients most likely due to the longer time from the symptom onset.…”
Section: Discussionmentioning
confidence: 42%
“…22,46 Similarly, an independent association of high admission serum ferritin levels with unfavorable outcomes has been found in patients with intracerebral hemorrhage. 47,48 In our study, the iron overload status was more pronounced in nonsurvivors, but it was not associated with hemorrhagic transformation or disability. Transferrin levels were lower in untreated patients most likely due to the longer time from the symptom onset.…”
Section: Discussionmentioning
confidence: 42%
“…From three studies reporting on ferritin and clinical outcome 29 , 32 , 105 , two studies of 155 participants measuring ferritin upon admission were included in a meta-analysis 29 , 32 . Neither of these studies included a multivariable analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, research has continued to reveal an association between elevated ferritin and various neuropathologies, such as neurovascular, neurodegenerative, and neuroautoimmune diseases [12,[30][31][32]. In such diseases, ferritin may become overwhelmed and no longer able to maintain proper homeostasis within the brain [27].…”
Section: Fe 2+mentioning
confidence: 99%
“…Preclinical studies have shown a vasoconstrictive effect from iron-containing hemin, and Gomes et al [34] performed a pilot study showing that levels of nonprotein-bound iron were significantly higher in patients who developed vasospasm after aneurysmal SAH [62]. A recent study by Rajendran et al [30] used serum ferritin as a prognostic marker in acute hemorrhagic stroke and found that elevated ferritin on admission indicated poor short-term and long-term outcomes using a modified Rankin scale, an extensive stroke scoring system. Therefore, CNS pathology is likely not due to iron overload, and the ferritin aggregates likely independently lead to significant disease manifestations.…”
Section: Targeting Ferritin Clearancementioning
confidence: 99%